Mission design for the VELOX- Lyon-1 (rebranded SCOOBI) student CubeSat - Luo, Ruikang (2019)
Since the first cube satellites were launched in 1994, the government has become more open in the civil aerospace industry due to the advantages of satellite technology and the low cost-barrier. Mission design, which contains orbit simulation, link budget and power budget calculation, is essential before each launch of satellite to ensure the feasibility and success rate. In the project, the Satellite Tool Kit was used to simulate the orbit characteristics for SCOOBI to choose the most suitable orbit under the constraints of requirements. Referred other subsystems and collaborated with other groups to get useful parameters’ value to figure out the uplink and downlink budget for Telecommunication subsystem. MATLAB was used for investigating the status of solar panels on SCOOBI and plotting the diagrams of power generation and state of charge. The suitable orbit was chosen. The communication link budget and power budget were calculated. The power generated and consumption were also figured out. The proposed Electrical Power Subsystem was verified to be feasible and competent for this operation.